Anti-feminism and Decadent Individualism: The Case of Rachilde (Pourquoi je ne suis pas féministe, 1928) - Boldrini, Emmanuel (Thélème. Revista Complutense de Estudios Franceses, 2026)
This article offers a reading of a particular essay by Rachilde (Pourquoi je ne suis pas féministe, 1928), understood as a late testimony to the motives underlying the author’s explicit refusal to join the feminist movements and the collective forms of female sociability of her time. The analysis conducted here sheds light in particular on a form of anti-feminism still deeply informed by decadent individualism. Rather than reducing Rachilde to a univocal ideological position, the article examines the tensions between authorial posture, polemical ethos, decadent imagination, and the history of first-wave feminisms.